PENGARUH MADDEN-JULLIAN OSCILLATION TERHADAP VARIABILITAS SUHU PERMUKAAN LAUT DI SELAT MAKASSAR - Rahmah, Ainiyah; Baeda, Achmad Yasir (Riset Sains dan Teknologi Kelautan, 2024)
Madden-Jullian Oscillation (MJO) climate variability is global climate variability that can influence oceanographic conditions, including sea surface temperature. This research was conducted to determine the influence of the MJO phenomenon on sea surface temperature variability during the Asian Monsoon period in the Makassar Strait. The data used in this research are MJO monitoring data from BOM, sea surface temperature data from NOAA's Aqua MODIS Satellite. The method used in this research is to group active MJO events into phases 2, 3, 4 and 5 and then create a monthly average SST. Next, determine the monthly SST anomaly and then analyze it. The research results show that when the MJO is active in phases 2,3,4 and 5, there is an increase and decrease in SST